Interference and Priority Aware Coexistence (IPC) Algorithm for Link Scheduling in IEEE 802.15.6 Based WBANs - Khan, F.N. (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper presents an Interference and Priority aware Coexistence (IPC) algorithm to ensure coexistence between multiple WBANs communicating within each other transmission range. By intelligently keeping an interfering WBAN silent, the IPC approach aims to maximize simultaneous (interference-free) transmissions from sensor nodes of different WBANs. Coordinators use beacons to exchange interference and priority aware metrics. This information is later used to generate an interference graph of the sensors associated with the coordinator and perform link scheduling. The IPC approach has been evaluated for two different interference scenarios namely, a High interference scenario which considers interference from the highest interfering coordinator or sensor node of all coexisting WBANs, and a Moderate interference scenario (conventionally used in the existing literature) which considers interference from the coordinator only. Considering the mobility of WBANs, the performance of IPC is evaluated in terms of spatial reuse, system throughput, delay, and packet delivery rate. IPC shows significant improvement in all performance metrics over existing schemes. Â© 2019 IEEE.